2011
DOI: 10.1002/jhet.668
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antimicrobial activity of substituted [(pyrazol‐4‐yl)methylene]hydrazono‐2,3‐dihydrothiazoles and their sugar derivatives

Abstract: A number of new [(pyrazol-4-yl)methylene]hydrazono-2,3-dihydrothiazole derivatives, their sugar hydrazones and N-glycosides were synthesized. Furthermore, N-substituted oxygenated alkyl and hydroxyl derivatives and 1,3,4,-oxadiazoline acyclic nucleoside analogs were prepared. The newly synthesized compounds were tested for their antimicrobial activities and showed moderate to high inhibition activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 48 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…al. reported the synthesis of many heterocycles from enaminones as starting material [23]. Many pyridine derivatives were reported from our lab [24,25].…”
Section: Results and Discussonmentioning
confidence: 99%
“…al. reported the synthesis of many heterocycles from enaminones as starting material [23]. Many pyridine derivatives were reported from our lab [24,25].…”
Section: Results and Discussonmentioning
confidence: 99%
“…The 1 HNMR showed chemical shifts at δ 2.95 and 3.18 ppm as singlet signals due to two CH 3 groups, doublets at δ 5.66 and 7.68 ppm due to two CH protons, in addition to, doublets at δ 7.85 and 8.70 ppm corresponding to pyridine (AB system). Furthermore, a molecular ion peak at m/z = 176 appeared in its mass spectrum due to the chemical formula C 10 H 12 N 2 O. Fadda et al [ 23 ] reported the synthesis of many heterocycles from enaminones as starting material. Many pyridine derivatives were reported from our lab.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the initial monoacetyl-substituted products are gradually converted to diacetyl substituted thiadiazoline 10 4.1H-NMR spectrum of compound 4 showed a signal at δ 2.16, δ 2.19, δ 2.26 ppm corresponding to three CH 3 groups and multiplet signal at δ 6.93-7.28 ppm for the aromatic protons and CH-5 of1,3,4-thiadiazoline ring. The mass spectrum of compound 4 showed the molecular ion peak at m/z 547 corresponding to the molecular formula C 27 H 23 Br N 4 O 2 S. Furthermore, treatment of thiosemicarbazone derivative 2a with phenacyl bromides in boiling ethanol in the presence of anhydrous sodium acetate 11 yielded the corresponding 3-[1,3-thiazol-2(3H)-ylidene]hydrazonomethyl-1H-indole derivative 5.1H-NMR spectrum of 5 showed a signal at δ 6.58 ppm corresponding to CH-5 of thiazole ring and signal at δ 8.30 ppm for an N=CH proton .The mass spectrum of compound 5 showed the molecular ion peak at m/z 563 corresponding to the molecular formula C 31 H 23 BrN 4 S. Refluxing thiosemicarbazone derivative 2a with chloroacetic acid in the presence of anhydrous sodium acetate in glacial acetic acid 12 afforded 1,3-thiazolidin-4-one derivative 6 (Scheme 1). IR spectra of 6 showed the disappearance of NH bands of substituted thiosemicarbazone moiety and the presence of a new band at 1703 cm −1 attributed to a carbonyl group of thiazolidin-4-one.…”
Section: Results and Discussion A) Chemistrymentioning
confidence: 99%